High English Literacy among Students from Low Socioeconomic Backgrounds: Exploring the Challenges - Muhamad Zamani, Nur Fadzilah (IIUM Journal of Educational Studies, 2018)
As people agree that socioeconomic status (SES) is one of the contributing factors that hinders one’s literacy development, there are still students who come from low socioeconomic background yet are able to acquire high English literacy despite the presence of life stressors. This study examines the challenges faced by low SES students in acquiring high English literacy and the factors that help them to overcome those challenges. Three students aged fourteen to sixteen years old were chosen as the sample for this study through purposive sampling technique. A qualitative semi-structured interview was conducted to obtain in-depth information about the topic discussed. Three themes emerged which include individual, family and school that demonstrated the challenges faced by low SES students in acquiring high English literacy and the factors that helped them to overcome those challenges. In brief, the participants agreed that their internal motivation and hard work were the most important factors that kept them positive to fight against challenges and become highly literate in the English language. Keywords: Semi-structured interview, qualitative, socioeconomic status (SES), English literacy, motivation